Telaah Metafisik Ritual Dolop Dalam Masyarakat Dayak Agabag - Satria Satria; Viktorius Siga; Bernardus Subang Hayong; Laurensius Anselmus Wae Woda (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
In the effort to explore the true dimensions of life, humans should not focus solely on the empirical and a priori levels. To achieve a deeper understanding, one must free oneself from all forms of attachment to things that are empirical and a priori. Deep reflection is necessary so that the fundamental principles can be discovered, leading to a more essential understanding of reality. This paper aims to analyze the metaphysical dimension contained within the dolop ritual. The findings of this study show that metaphysical reflection can overcome the limited view of reality that is apparent on the surface, which often feels "real" but is actually deceptive. Unknowingly, such views fall into the ideological realm that restricts and binds, causing humans to become trapped in the sacralization of space, time, and place that color the Kasada ritual ceremony. Based on these findings, the study of the metaphysical dimension continues by delving deeper into the existence and meaning of the symbols present. This exploration ultimately concludes that the metaphysical dimension in the dolop ritual of the Dayak Agabag community is, in fact, a representation or miniature of life itself. This ritual is not merely a ceremony, but a broader representation of life that must be understood in a deeper context.